Effect of osmotic stress on root architecture and defensive system in wheat genotypes at seedling stage - sheoran, sonia; Mittal, Vandita; Singh, Narender; Narwal, Sneh; HM, Mamrutha; Tiwari, Vinod; Sharma, Indu (Journal of Cereal Research, 2015)
The present investigation was conducted to assess the changes in root architecture and defensive system in contrasting genotypes under PEG induced osmotic stress and to determine the optimum osmotic stress level, which could differentiate the drought resistance among genotypes. Changes in physiological and biochemical characteristics were also evaluated. Seedlings were subjected to osmotic stress by supplementing root medium with three different concentrations of PEG 6000. Results highlighted statistically significant differences in most of the traits for treatment T4 (-1.00MPa) as critical for differentiating the drought tolerant and drought susceptible genotypes at seedling stage itself. Â Water status and chlorophyll content decreased in all the concentrations of PEG. Increase in the activities of superoxide dismutase and catalase enzyme was observed in drought tolerant genotypes C306 and PBW175 which also suggested their water stress tolerance behavior in comparison to other genotypes. This study provides evidence that the tolerant genotypes are well equipped with better physiological traits and good defensive system. This seedling assay could be used by wheat breeders in their breeding programmes to select drought tolerant wheat genotypes at an early stage.